A novel approach for the evaluation of the economical losses due to seismic actions on RC buildings with masonry infills. Issue 145 (June 2021) - Rossi, A.; Morandi, P.; Magenes, G.
Abstract: A novel approach to evaluate the seismic performance of RC frame buildings with masonry infill walls is proposed, based on the PERR's PBEE procedure, taking into account both structural response and the computation of economic losses, consequence of the damage in the building components. A case-study on a plane infilled RC frame is presented, considering three "traditional typologies" of masonry infill walls compared with an innovative infill solution with sliding joints. The definition of infill damage was inferred directly by laboratory tests and by numerical simulations and the computation of losses is referred to updated official costs of repair and replacement actually adopted in Italy. Lastly, the evaluation of the seismic performance in terms of expected annual loss of a building with specific indications on infill typologies allows a consistent comparison on the effective contribution of different infill solutions and an estimation of the economic benefits that the use of the innovative infill systems could provide as respect to traditional infills. Highlights: Novel approach evaluating seismic performance of RC frame buildings with masonry infill, based on the PEER's PBEE procedure. Compare the structural and economical performance of RC frame with both tradition and innovative infills. The definition of damage in all infills is inferred directly by lab-tests and numerical simulations. Losses are referred to updated official costs of repair and replacement actually adopted in Italy.